Competency Skills and Use of Ict by Teacher Educators in Imo State Tertiary Institutions - Anyanwu, Julius Okechukwu; Ekechukwu, Leona Eucheria; Ettu, Theresa U.; Ndunagu, Juliana Ngozi; Faustina, Eleanya (American Journal of Education and Learning, 2016)
The study surveyed the competency skills and use of ICT by teacher educators in Imo State tertiary institutions. To elicit responses for the study, four research hypotheses were formulated. Two hundred and forty (240) lecturers, 48 lecturers, from Imo State University Owerri and 192 lecturers from Alvan Ikoku Federal College of education, Owerri participated in the study. Data were collected for the study through the administration of 27 item structured questionnaire was validated and was also subjected to reliability which has internal consistency of 0.78r was used for data collection. A test re-test method was used to determine the reliability of the instrument, the resulted was appropriately scored. The data obtained were analyzed using both descriptive and inferential statistics of t-test in testing the hypotheses. The findings showed that gender has no effects on the procession and use of ICT into teaching and learning by teacher educators in tertiary institution. Less experienced lecturers are more exposed in use of ICT than high experienced lecturers. Some lecturers lacked adequate training and competence in using computer as a tool for effective teaching and research work. The study was recommended that higher institutions should encourage their lecturers to be sensitized through conferences, seminars and workshops. The old lecturers should be encouraged to develop good attitudes toward the use of ICT for teaching and research purpose. Recommendations were made towards effective use of ICT skills in tertiary institutions by teacher educators in Nigeria.